The Influence of the Role of Guru Penggerak on the Pedagogical Competence of Senior High School Teachers in Blora Regency - Farida Listyari; Rosalina Br Ginting; Endang Wuryandini (Dinasti International Journal of Education Management And Social Science, 2025)
Teachers' pedagogical competence is one of the essential aspects of improving the quality of education. To enhance teachers' pedagogical competence, several factors need to be examined, one of which is the role of Guru Penggerak. Guru Penggerak plays a crucial role in driving change in schools by acting as a coach for other teachers, fostering collaboration, and mobilizing practitioner communities. This study aims to analyze the influence of the role of Guru Penggerak on the pedagogical competence of senior high school teachers in Blora Regency. Data collection was conducted through questionnaires distributed to 175 teachers from 8 senior high schools in Blora Regency. Data analysis utilized regression analysis to measure the effect of the independent variable on the dependent variable. The results of the study indicate that the role of Guru Penggerak has a positive and significant influence on teachers' pedagogical competence, with the regression equation ? = 144.468 + 0.286X, a correlation strength of 0.523, and an effect of 27.4%. Based on these findings, it can be concluded that the role of Guru Penggerak has a positive and significant impact on the pedagogical competence of senior high school teachers in Blora Regency, contributing 27.4%. A recommendation from this study is for Guru Penggerak to be actively engaged in their role in mobilizing practitioner communities and encouraging collaboration among teachers.